Configurações do homoerotismo feminino no romance "As Traças" de Cassandra Rios - Cantalice, Juviniano Gomes de (2011)
The speeches concerning the (homo) sexual identities have been creating a significant infinity of debates the issues concerning the very notion of identity that, by itself, is already a complex issue in nowadays;on the other hand, it has been discussing plenty the place of it belongs of the called cultural minorities in a world that has not yet learned enough to live with diversity.In that context, therefore, of the discussions around the cultural differences and, in matter, the sexual differences, we intend to investigate, in work of dissertation of Master's degree, in the line of Sociocultural research for the Literature", "the homoerotic female representation in the work As Traças (2005), of the writer from São Paulo Cassandra Rios, with the objective of investigating the course of construction of the character's subjectivity Andréa.Thus, we anxious about the issue around how such subjectivity is constructed and how it fits in homoerotic language to enable the main character Andrea social visibility , cultural, and especially sexual. Thus, the author builds her main character s course/journey and she makes this showing its hard path of statement of an identity seen by the other members of the society as "different", "deviant", "pathological." For this research some theorists that discuss questions about gender and sexuality will support us, they are, them, namely: Butler (2008), Facco (2004), Zinani (2006), Louro (2008), Foucault (1979; 1997; 1998), and others who in one way or another discuss the subjects of gender and sexuality in the context of cultural studies.